Aktor Pendorong Kebijakan Pengurangan Produksi Minyak Opec Di Era Pandemi Covid-19 Tahun 2020 - Inti Qoun Naji; Ali Martin (Kajian Hubungan Internasional, 2021)
This research is based on true changes caused by the spread of COVID-19 in 2020, it influences all world’s industry sectors. This situation ruins all the export-import process. OPEC’s largest oil-exporting country decided to cut production policies to stabilize the situation. This research aims to find out the factors that affect OPEC's oil production cuts in 2020.In this study, the authors use explanatory research to explain the factors driving production cuts. From the results of the study, it was found that there were several causes of OPEC production cuts.  They are the abundance of goods, conflicts between member countries, the competition from non-OPEC organizations, lockdown, activities restrictions enforcement, and industrial production activities restrictions. Internal and external factors strongly encourage OPEC's oil production cut policy.